Implementation of disability policy framework in Namibia: A qualitative study - Tonderai W. Shumba; Indres Moodley (AOSIS, 2018)
Background: This study explores some of the experiences of national programme managers, heads of national organisations of persons with disabilities (OPDs) and persons with disabilities in the implementation of the disability policies and legal framework in Namibia. Method: In-depth interviews were conducted with multiple key stakeholders mentioned above. Interviews were digitally recorded and transcribed verbatim. The Community Based Rehabilitation (CBR) matrix (health, education, livelihood, social and empowerment) was utilised to guide the development of themes and subthemes. Results: Twenty-one key informants participated in the study. Participants stated that while Namibia has made significant progress in addressing the medical and social needs of persons with disabilities, further progress can be achieved through better coordination, capacity building, review and updating of policies which allows for the inclusion of personal assistance, access to justice, improving supply chain management for a wide range of assistive devices, mainstreaming HIV prevention and treatment programmes, improved access to sexual reproduction and family planning, improved access to higher education, curricula reviews and effective monitoring and evaluating of the CBR programme. Conclusions: The study revealed key issues that need to be addressed in reviewing the policy and legal framework so that it is responsive to the current needs of persons with disabilities. Further, the CBR programme needs an evaluation tool to assess its effectiveness and efficiency in meeting the needs of persons with disabilities and also to elicit their experiences and satisfaction.